Chronic Diarrhea Associated with High Teriflunomide Blood Concentration. Issue 1 (June 2016) - Duquette, André; Frenette, Anne; Doré, Maxime
Abstract Objective To report the case of a patient treated with leflunomide that presented with chronic diarrhea associated with high teriflunomide blood concentration. Case Summary An 84-year-old woman taking leflunomide 20 mg once daily for the past 2 years to treat rheumatoid arthritis (RA) was investigated for severe chronic diarrhea that had been worsening for the past 5 months. The patient's general condition progressively deteriorated and included electrolyte imbalances and a transient loss of consciousness. Therefore, hospitalization was required. Teriflunomide blood concentration was 156 mg/L. After 11 days of cholestyramine washout therapy, teriflunomide blood concentration was reduced to 6 mg/L. As the teriflunomide levels decreased, diarrhea improved. All other possible causes of diarrhea were ruled out. The patient's diarrhea finally resolved 26 days after treatment with cholestyramine. Discussion Diarrhea is a known adverse effect of leflunomide. In this report, the severe diarrhea was associated with high blood teriflunomide concentrations. Available data suggests an association between teriflunomide concentrations greater than 50 mg/L and lower disease activity, but toxic teriflunomide levels still have to be clarified. Conclusion Further studies are needed to establish the optimal therapeutic levels of teriflunomide. However, therapeutic drug monitoring of teriflunomide blood concentrations may be helpful to improve effectiveness and to prevent toxicity in patients taking leflunomide for RA, particularly in those with suboptimal therapeutic response to leflunomide or in patients with toxicity suspected to be induced by leflunomide.